A kind of high strength gypsum mortar and preparation method thereof

Through the combination of modified polyurethane and other additives, the compressive strength and water resistance of gypsum mortar are improved, and the problem of insufficient performance of traditional gypsum mortar is solved, and the preparation of gypsum mortar with high strength and water resistance is achieved, which is suitable for the construction field.

CN118851707BActive Publication Date: 2025-01-03JIANGYIN TIANBANG ENVIRONMENTAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326470.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The compressive strength and water resistance of traditional gypsum mortar are insufficient, making it difficult to meet the construction industry's demand for high strength and water resistance.

Method used

Using modified polyurethane, glass fiber, mica powder and diatomaceous earth, high-strength gypsum mortar is prepared through specific process steps. The modified polyurethane is reacted by epoxy soybean oil-based polyol and isocyanate-based, and fluorine-containing silicone is added to improve the Adhesion and water resistance.

Benefits of technology

It significantly improves the strength, adhesion and water resistance of gypsum mortar, enhances the adhesion ability to the wall, reduces the water absorption rate, and is suitable for a wide range of applications in the construction field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and discloses a high-strength gypsum mortar and a preparation method thereof. The gypsum mortar of the present invention comprises the following raw materials in parts by weight: 60-70 parts of gypsum powder, 20-30 parts of modified polyurethane, 5-8 parts of glass fiber, 5-8 parts of diatomaceous earth, 7-10 parts of mica powder, 2-4 parts of water reducer, 1-2 parts of retarder, 0.5-1 parts of thickener, 10-15 parts of silicate cement, 0.5-1 parts of glue powder, and 70-90 parts of deionized water; it is by adding modified polyurethane, the strength, adhesion and water resistance of the matrix are improved; the addition of glass fiber improves the mechanical properties of the matrix; the addition of mica powder improves the hardness and strength of the matrix; the addition of other additives, synergistically, improves the overall performance of the matrix; therefore, the gypsum mortar of the present invention can be widely used in the field of construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a high-strength gypsum mortar and a preparation method thereof. Background Art

[0002] Gypsum mortar is a new type of building material. It is a mortar made of gypsum as the main raw material, mixed with an appropriate amount of inorganic fillers and additives. Gypsum mortar has the characteristics of good adhesion, fast hardening, high compressive strength, and water resistance. Therefore, it is widely used in the construction industry. It can be used for plastering, leveling, and tile pasting on indoor and outdoor walls, floors, ceilings, etc. However, with the increase in actual application needs, the compressive strength and water resistance of traditional gypsum mortar are no longer applicable, and it is necessary to adopt appropriate methods to improve the performance of gypsum mortar. Common modification methods of gypsum mortar are: (1) improving the strength of gypsum mortar by adding inorganic powders; (2) adding polymer emulsions, siloxanes and other materials to improve the structure and porosity of gypsum mortar, thereby improving its water resistance.

[0003] Polyurethane has excellent flexibility, adhesion, wear resistance and compressive strength. Adding it to gypsum mortar as a modified material can not only improve the adhesion between the mortar and the wall, but also improve the strength of the gypsum mortar. However, since the water resistance of polyurethane itself is not good enough, it is necessary to modify polyurethane to improve its water resistance, thereby improving the water resistance of gypsum mortar. Therefore, researchers need to prepare a high-strength, water-resistant, and excellent bonding gypsum mortar to meet actual needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-strength gypsum mortar and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-strength gypsum mortar, comprising the following raw materials in parts by weight: 60-70 parts of gypsum powder, 20-30 parts of modified polyurethane, 5-8 parts of glass fiber, 5-8 parts of diatomaceous earth, 7-10 parts of mica powder, 2-4 parts of water reducing agent, 1-2 parts of retarder, 0.5-1 parts of thickener, 10-15 parts of silicate cement, 0.5-1 parts of rubber powder, and 70-90 parts of deionized water;

[0007] The modified polyurethane is prepared by the following steps:

[0008] Step A1, adding epoxidized soybean oil and sodium hydroxide into a reactor containing anhydrous ethanol and stirring evenly, then adding trishydroxymethylaminomethane, and stirring at a speed of 500-700 rpm for 2-3 hours. After the reaction is completed, vacuum distillation, filtering, washing, and drying are performed to obtain soybean oil-based polyol;

[0009] Step A2, adding soybean oil-based polyol and polyester polyol into a flask, heating to 70-80° C. under nitrogen, and stirring evenly at a speed of 240 rpm, then adding isophorone diisocyanate and dibutyltin dilaurate, stirring and reacting for 3-4 hours, then adding 2,2-dihydroxymethylbutyric acid and butanone to continue reacting for 2 hours, after the reaction is completed, cooling to 40° C., adding triethylamine and stirring for 30 minutes to obtain a polyurethane prepolymer, lowering the temperature of the polyurethane prepolymer to room temperature, using a dropping funnel to dropwise add fluorinated silicone to react for 30-60 minutes, after the reaction is completed, cooling to room temperature, adding deionized water and stirring for 1 hour, and rotary evaporation to obtain a modified polyurethane;

[0010] Specifically, in step A1, the usage ratio of epoxidized soybean oil, sodium hydroxide, anhydrous ethanol and tris(hydroxymethyl)aminomethane is 0.01-0.03 mol: 0.03-0.06 g: 100 mL: 0.08-0.24 mol;

[0011] Specifically, in step A2, the dosage ratio of soybean oil-based polyol, polyester polyol, isophorone diisocyanate, dibutyltin dilaurate, 2,2-dihydroxymethylbutyric acid, butanone, triethylamine, fluorinated silicone and deionized water is 10-15g: 15-25g: 20-26g: 0.05-0.1g: 1.5-3.5g: 3-6mL: 5-8g: 3-6g: 10-20mL.

[0012] The fluorine-containing silicone is prepared by the following steps:

[0013] Methyltriethoxysilane, benzyltriethoxysilane, 4-aminobutyltriethoxysilane and 1H, 1H, 2H, 2H-nonafluorohexyltrimethoxysilane are added to tetrahydrofuran and stirred to mix evenly. Under stirring conditions, 0.1 mol / L hydrochloric acid solution is added, and after stirring and reacting for 24 hours, the system temperature is increased to 45-65° C. and refluxed for 24 hours. After the reaction is completed, rotary evaporation, extraction, water washing and drying are performed to obtain fluorinated organosilicon;

[0014] Specifically, the usage ratio of methyltriethoxysilane, benzyltriethoxysilane, 4-aminobutyltriethoxysilane, 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane and hydrochloric acid solution in the fluorine-containing silicone is 0.2-0.3 mol: 0.05-0.08 mol: 0.1-0.15 mol: 0.1-0.2 mol: 200 mL: 7-11 g.

[0015] A method for preparing high-strength gypsum mortar comprises the following steps:

[0016] Weigh the raw materials by weight, add gypsum powder, diatomaceous earth, mica powder, silicate cement and rubber powder into a ball mill, and ball-mill into 200-300 mesh powder, then transfer the powder to a blender, add a water reducer, a retarder, a thickener, a modified polyurethane and glass fiber, stir and mix evenly, then add deionized water and stir for 20-30 minutes to obtain a high-strength gypsum mortar.

[0017] Beneficial effects of the present invention:

[0018] The gypsum mortar of the present invention improves the strength, adhesion and water resistance of the base by adding modified polyurethane; the addition of glass fiber improves the mechanical properties of the base; the addition of mica powder improves the hardness and strength of the base and reduces the water absorption of the gypsum mortar; the addition of other additives synergistically improves the overall performance of the base; therefore, the gypsum mortar of the present invention can be widely used in the field of construction.

[0019] In the modified polyurethane, firstly, the epoxy group in epoxidized soybean oil is reacted with the amino group in trimethylolaminomethane to generate soybean oil-based polyol; secondly, the polyurethane prepolymer is synthesized using soybean oil-based polyol and polyester polyol as polyols, and fluorinated silicone is used as a modifier. The amino group in the fluorinated silicone is reacted with the isocyanate group in the polyurethane prepolymer to obtain the modified polyurethane. After the modified polyurethane is added to the matrix, the strength, adhesion and water resistance of the gypsum mortar are improved. This is because the silicone introduced into the modified polyurethane contains siloxane, which can be hydrolyzed into silanol, which can react with mica powder, cement and hydroxyl groups on the wall surface, thereby improving the self-strength of the gypsum mortar and the adhesion between the gypsum mortar and the wall; at the same time, due to the reaction of the amino group in the silicone with the isocyanate group, a polar group (urea group) is introduced, which enhances the intermolecular force of the polyurethane. The enhanced intermolecular force and the synergistic effect of the rigid benzene ring structure hinder the diffusion and penetration of water molecules in the matrix and improve the water resistance of the matrix; the fluorine-containing segment in the silicone segment has a lower surface energy and gradually moves to the surface of the matrix during the curing process, thereby improving the waterproofness of the matrix and thus improving the strength of the matrix; in addition, the soybean oil-based polyol acts as a cross-linking agent in the modified polyurethane to form a dense three-dimensional network structure, which weakens the diffusion and penetration ability of water molecules in the matrix and thus improves the strength of the matrix. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1: (1) Fluorine-containing silicone is prepared by the following steps:

[0022] 0.2 mol of methyltriethoxysilane, 0.05 mol of benzyltriethoxysilane, 0.1 mol of 4-aminobutyltriethoxysilane and 0.1 mol of 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane were added into 200 mL of tetrahydrofuran and stirred to mix evenly. Under stirring condition, 7 g of 0.1 mol / L hydrochloric acid solution was added. After stirring for 24 hours, the system temperature was increased to 45°C and refluxed for 24 hours. After the reaction was completed, rotary evaporation, extraction, water washing and drying were carried out to obtain fluorinated silicone.

[0023] (2) The modified polyurethane is prepared by the following steps:

[0024] Step A1, add 0.01 mol of epoxidized soybean oil and 0.03 g of sodium hydroxide into a reactor containing 100 mL of anhydrous ethanol and stir evenly, then add 0.08 mol of tris(hydroxymethyl)aminomethane, and stir at a speed of 500 rpm for 2 h. After the reaction is completed, vacuum distillation, filtration, washing, and drying are performed to obtain soybean oil-based polyol;

[0025] Step A2, 10g soybean oil-based polyol and 15g polyethylene adipate (molecular weight 2000) were added to a flask, heated to 70°C under nitrogen, and stirred evenly at a speed of 240rpm, then 20g isophorone diisocyanate and 0.05g dibutyltin dilaurate were added, stirred for reaction for 3h, and then 1.5g 2,2-dihydroxymethylbutyric acid and 3mL butanone were added to continue the reaction for 2h. After the reaction was completed, the temperature was lowered to 40°C, 5g triethylamine was added and stirred for 30min to obtain a polyurethane prepolymer, the temperature of the polyurethane prepolymer was lowered to room temperature, 3g fluorinated silicone was added dropwise using a dropping funnel to react for 30min, after the reaction was completed, it was cooled to room temperature, 10mL deionized water was added and stirred for 1h, and rotary evaporated to obtain a modified polyurethane.

[0026] Example 2: (1) Fluorine-containing silicone is prepared by the following steps:

[0027] 0.25 mol of methyltriethoxysilane, 0.07 mol of benzyltriethoxysilane, 0.12 mol of 4-aminobutyltriethoxysilane and 0.15 mol of 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane were added into 200 mL of tetrahydrofuran and stirred to mix evenly. Under stirring condition, 9 g of 0.1 mol / L hydrochloric acid solution was added. After stirring for 24 hours, the system temperature was increased to 55°C and refluxed for 24 hours. After the reaction was completed, rotary evaporation, extraction, water washing and drying were carried out to obtain fluorinated silicone.

[0028] (2) The modified polyurethane is prepared by the following steps:

[0029] Step A1, 0.02 mol of epoxidized soybean oil and 0.045 g of sodium hydroxide were added to a reactor containing 100 mL of anhydrous ethanol and stirred evenly, and then 0.16 mol of tris(hydroxymethyl)aminomethane was added and stirred at a speed of 600 rpm for 2.5 h. After the reaction was completed, the mixture was distilled under reduced pressure, filtered, washed and dried to obtain soybean oil-based polyol;

[0030] Step A2, 12g soybean oil-based polyol and 20g polyethylene adipate (molecular weight 2000) were added to a flask, heated to 75°C under nitrogen, and stirred evenly at a speed of 240rpm, then 23g isophorone diisocyanate and 0.075g dibutyltin dilaurate were added, stirred for reaction for 3.5h, and then 2.5g 2,2-dihydroxymethylbutyric acid and 4.5mL butanone were added to continue the reaction for 2h. After the reaction was completed, the temperature was lowered to 40°C, 6.5g triethylamine was added and stirred for 30min to obtain a polyurethane prepolymer, the temperature of the polyurethane prepolymer was lowered to room temperature, 4.5g fluorinated silicone was added dropwise using a dropping funnel to react for 45min, and after the reaction was completed, it was cooled to room temperature, 15mL deionized water was added and stirred for 1h, and rotary evaporated to obtain a modified polyurethane.

[0031] Example 3: (1) Fluorine-containing silicone is prepared by the following steps:

[0032] 0.3 mol of methyltriethoxysilane, 0.08 mol of benzyltriethoxysilane, 0.15 mol of 4-aminobutyltriethoxysilane and 0.2 mol of 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane were added into 200 mL of tetrahydrofuran and stirred to mix evenly. Under stirring condition, 11 g of 0.1 mol / L hydrochloric acid solution was added. After stirring for 24 hours, the system temperature was increased to 65°C and refluxed for 24 hours. After the reaction was completed, rotary evaporation, extraction, water washing and drying were carried out to obtain fluorinated silicone.

[0033] (2) The modified polyurethane is prepared by the following steps:

[0034] Step A1, add 0.03 mol of epoxidized soybean oil and 0.06 g of sodium hydroxide into a reactor containing 100 mL of anhydrous ethanol and stir evenly, then add 0.24 mol of tris(hydroxymethyl)aminomethane, and stir at a speed of 700 rpm for 3 h. After the reaction is completed, vacuum distillation, filtration, washing, and drying are performed to obtain soybean oil-based polyol;

[0035] Step A2, 15g soybean oil-based polyol and 25g polyethylene adipate (molecular weight 2000) were added to a flask, heated to 80°C under nitrogen, and stirred evenly at a speed of 240rpm, then 26g isophorone diisocyanate and 0.1g dibutyltin dilaurate were added, stirred for reaction for 4h, and then 3.5g 2,2-dihydroxymethylbutyric acid and 6mL butanone were added to continue the reaction for 2h. After the reaction was completed, the temperature was lowered to 40°C, 8g triethylamine was added and stirred for 30min to obtain a polyurethane prepolymer, the temperature of the polyurethane prepolymer was lowered to room temperature, 6g fluorinated silicone was added dropwise using a dropping funnel to react for 60min, and after the reaction was completed, it was cooled to room temperature, 20mL deionized water was added and stirred for 1h, and rotary evaporated to obtain a modified polyurethane.

[0036] Embodiment 4: A method for preparing high-strength gypsum mortar, comprising the following steps:

[0037] 60 parts of gypsum powder, 20 parts of modified polyurethane prepared in Example 1, 5 parts of glass fiber, 5 parts of diatomaceous earth, 7 parts of mica powder, 2 parts of naphthalenesulfonate formaldehyde condensate, 1 part of sodium citrate, 0.5 parts of ethoxylated alkyl sodium sulfide, 10 parts of Portland cement, 0.5 parts of rubber powder, and 70 parts of deionized water;

[0038] The raw materials were weighed according to weight, and gypsum powder, diatomaceous earth, mica powder, silicate cement and rubber powder were added into a ball mill and ball-milled into a powder of 200 mesh. The powder was then transferred to a blender, and naphthalenesulfonate formaldehyde condensate, sodium citrate, ethoxylated alkyl sodium sulfide, the modified polyurethane prepared in Example 1 and glass fiber were added and stirred to mix evenly. Deionized water was then added and stirred for 20 minutes to obtain a high-strength gypsum mortar.

[0039] Embodiment 5: A method for preparing high-strength gypsum mortar, comprising the following steps:

[0040] 65 parts of gypsum powder, 25 parts of modified polyurethane prepared in Example 2, 6 parts of glass fiber, 6 parts of diatomaceous earth, 8 parts of mica powder, 3 parts of naphthalenesulfonate formaldehyde condensate, 1.5 parts of sodium citrate, 0.7 parts of ethoxylated alkyl sodium sulfide, 12 parts of Portland cement, 0.7 parts of rubber powder, and 80 parts of deionized water;

[0041] The raw materials were weighed according to weight, and gypsum powder, diatomaceous earth, mica powder, silicate cement and rubber powder were added into a ball mill and ball-milled into a powder of 200 mesh. The powder was then transferred to a blender, and naphthalenesulfonate formaldehyde condensate, sodium citrate, ethoxylated alkyl sodium sulfide, the modified polyurethane prepared in Example 2 and glass fiber were added and stirred to mix evenly. Deionized water was then added and stirred for 25 minutes to obtain a high-strength gypsum mortar.

[0042] Embodiment 6: A method for preparing high-strength gypsum mortar, comprising the following steps:

[0043] 70 parts of gypsum powder, 30 parts of modified polyurethane prepared in Example 3, 8 parts of glass fiber, 8 parts of diatomaceous earth, 10 parts of mica powder, 4 parts of naphthalenesulfonate formaldehyde condensate, 2 parts of sodium citrate, 1 part of ethoxylated alkyl sodium sulfide, 15 parts of Portland cement, 1 part of rubber powder, and 90 parts of deionized water;

[0044] The raw materials were weighed according to weight, and gypsum powder, diatomaceous earth, mica powder, silicate cement and rubber powder were added into a ball mill and ball-milled into a 300-mesh powder. The powder was then transferred to a blender, and naphthalenesulfonate formaldehyde condensate, sodium citrate, ethoxylated alkyl sodium sulfide, the modified polyurethane prepared in Example 3 and glass fiber were added and stirred to mix evenly. Deionized water was then added and stirred for 30 minutes to obtain a high-strength gypsum mortar.

[0045] Comparative Example: This comparative example is a gypsum mortar, which is different from Example 6 in that an equal amount of polyurethane is used to replace the modified polyurethane prepared in Example 3, and the rest is the same; the polyurethane in this comparative example is prepared by the following steps:

[0046] 40 g of polyethylene adipate (molecular weight 2000) was added into a flask, heated to 80°C under nitrogen, and stirred evenly at 240 rpm. Subsequently, 26 g of isophorone diisocyanate and 0.1 g of dibutyltin dilaurate were added, and the mixture was stirred for 4 h. Then, 3.5 g of 2,2-dihydroxymethylbutyric acid and 6 mL of butanone were added and the reaction was continued for 2 h. After the reaction was completed, the temperature was lowered to 40°C, 8 g of triethylamine was added and stirred for 30 min to obtain a polyurethane prepolymer. The temperature of the polyurethane prepolymer was lowered to room temperature, and 4 g of propylene glycol was added dropwise using a dropping funnel and the reaction was carried out for 60 min. After the reaction was completed, the mixture was cooled to room temperature, 20 mL of deionized water was added and stirred for 1 h, and the mixture was rotary evaporated to obtain a polyurethane.

[0047] The performance tests were performed on the gypsum mortars of Examples 4-6 and the comparative example:

[0048] Compressive strength test: refer to the requirements of GB / T17669.3-1999 "Determination of Mechanical Properties of Building Gypsum" to maintain the test blocks, and check the compressive strength of the test blocks at the age of 7d and 28d;

[0049] Bonding performance test: refer to the industry standard JGJ / T220-2010 "Technical Specifications for Plastering Mortar" to test the tensile bonding strength;

[0050] Water absorption test: refer to the provisions of GB / T 5486.3-2001 "Test methods for density, moisture content and water absorption of inorganic rigid thermal insulation products", and test the water absorption at 7 days;

[0051] The test results are shown in the following table:

[0052]

[0053] As can be seen from the above table, the gypsum mortar prepared by the present invention is tested for compressive strength, bonding performance and water absorption. The compressive strength after 7d and 28d are 7.65MPa-8.04MPa and 17.54MPa-18.45MPa, respectively, the tensile bonding strength after 7d is 0.38MPa-0.47MPa, and the water absorption is 4.6%-5.1%, indicating that it has excellent strength, bonding performance and water resistance.

[0054] The compressive strength described above is merely an example and illustration of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength gypsum mortar, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of gypsum powder, 20-30 parts of modified polyurethane, 5-8 parts of glass fiber, 5-8 parts of diatomaceous earth, 7-10 parts of mica powder, 2-4 parts of water reducing agent, 1-2 parts of retarder, 0.5-1 parts of thickener, 10-15 parts of silicate cement, 0.5-1 parts of rubber powder and 70-90 parts of deionized water; The modified polyurethane is prepared by the following steps: Step A1, adding epoxidized soybean oil and sodium hydroxide into a reactor containing anhydrous ethanol and stirring evenly, then adding trishydroxymethylaminomethane, and stirring at a speed of 500-700 rpm for 2-3 hours. After the reaction is completed, vacuum distillation, filtering, washing, and drying are performed to obtain soybean oil-based polyol; Step A2, adding soybean oil-based polyol and polyester polyol into a flask, heating to 70-80° C. under nitrogen, and stirring evenly at a speed of 240 rpm, then adding isophorone diisocyanate and dibutyltin dilaurate, stirring and reacting for 3-4 hours, then adding 2,2-dihydroxymethylbutyric acid and butanone and continuing to react for 2 hours, after the reaction is completed, cooling to 40° C., adding triethylamine and stirring for 30 minutes to obtain a polyurethane prepolymer, lowering the temperature of the polyurethane prepolymer to room temperature, using a dropping funnel to add fluorinated silicone dropwise to react for 30-60 minutes, after the reaction is completed, cooling to room temperature, adding deionized water and stirring for 1 hour, and rotary evaporation to obtain a modified polyurethane.

2. A high-strength gypsum mortar according to claim 1, characterized in that: In step A1, the usage ratio of epoxidized soybean oil, sodium hydroxide, anhydrous ethanol and tris(hydroxymethyl)aminomethane is 0.01-0.03 mol: 0.03-0.06 g: 100 mL: 0.08-0.24 mol.

3. A high-strength gypsum mortar according to claim 1, characterized in that: In step A2, the dosage ratio of soybean oil-based polyol, polyester polyol, isophorone diisocyanate, dibutyltin dilaurate, 2,2-dihydroxymethylbutyric acid, butanone, triethylamine, fluorinated silicone and deionized water is 10-15g: 15-25g: 20-26g: 0.05-0.1g: 1.5-3.5g: 3-6mL: 5-8g: 3-6g: 10-20mL.

4. The high-strength gypsum mortar according to claim 1, characterized in that: The fluorine-containing silicone is prepared by the following steps: Methyltriethoxysilane, benzyltriethoxysilane, 4-aminobutyltriethoxysilane and 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane are added to tetrahydrofuran and stirred to mix evenly. Under stirring conditions, 0.1 mol / L hydrochloric acid solution is added. After stirring for 24 hours, the system temperature is increased to 45-65°C and refluxed for 24 hours. After the reaction is completed, rotary evaporation, extraction, water washing and drying are performed to obtain fluorinated silicone.

5. A high-strength gypsum mortar according to claim 4, characterized in that: The dosage ratio of methyltriethoxysilane, benzyltriethoxysilane, 4-aminobutyltriethoxysilane, 1H,1H,2H,2H-nonafluorohexyltrimethoxysilane and hydrochloric acid solution in the fluorine-containing silicone is 0.2-0.3 mol: 0.05-0.08 mol: 0.1-0.15 mol: 0.1-0.2 mol: 200 mL: 7-11 g.

6. The method for preparing a high-strength gypsum mortar according to claim 1, characterized in that: The following steps are involved: Weigh the raw materials by weight, add gypsum powder, diatomaceous earth, mica powder, silicate cement and rubber powder into a ball mill, and ball-mill into 200-300 mesh powder, then transfer the powder to a blender, add a water reducer, a retarder, a thickener, a modified polyurethane and glass fiber, stir and mix evenly, then add deionized water and stir for 20-30 minutes to obtain a high-strength gypsum mortar.